The role of assembly parameters on polyplex poly(beta‐amino ester) nanoparticle transfections. Issue 5 (29th January 2019) - Wilson, David R.; Suprenant, Mark P.; Michel, John H.; Wang, Ellen B.; Tzeng, Stephany Y.; Green, Jordan J.
Abstract: Intracellular delivery of nucleic acids to mammalian cells using polyplex nanoparticles (NPs) remains a challenge both in vitro and in vivo, with transfections often suffering from variable efficacy. To improve reproducibility and efficacy of transfections in vitro using a next‐generation polyplex transfection material poly(beta‐amino ester)s (PBAEs), the influence of multiple variables in the preparation of these NPs on their transfection efficacy was explored. The results indicate that even though PBAE/pDNA polyplex NPs are formed by the self‐assembly of polyelectrolytes, their transfection is not affected by the manner in which the components are mixed, facilitating self‐assembly in a single step, but timing for self‐assembly of 5–20 min is optimal. In addition, even though the biomaterials are biodegradable in water, their efficacy is not affected by up to eight freeze‐thaw cycles of the polymer. It was found that there is a greater stability of nucleic acid‐complexed polymer as a polyplex nanoparticle compared with free polymer. Finally, by exploring multiple buffer systems, it was identified that utilization of divalent cation magnesium or calcium acetate buffers at pH 5.0 is optimal for transfection using these polymeric materials, boosting transfection several folds compared with monovalent cations. Together, these results can improve the reproducibility and efficacy of PBAE and similar polyplex nanoparticle transfections and improve the robustness of using these biomaterials for bioengineering and biotechnology applications. Abstract : Wilson and coworkers assessed the assembly parameters affecting poly(beta‐amino ester)/DNA nanoparticle performance in vitro including the ratio of mixing for cationic polymer and plasmid DNA, the time allotted for polyplex assembly, freeze‐thaw stability, and buffer conditions. Their findings show improvements in using these polymeric materials as transfection reagents and demonstrate the robustness of poly(beta‐amino ester) nanoparticles for general use as a nucleic acid delivery tool.